2016
DOI: 10.1016/j.bbrc.2016.04.131
|View full text |Cite
|
Sign up to set email alerts
|

Role of ATF5 in the invasive potential of diverse human cancer cell lines

Abstract: Activating transcription factor 5 (ATF5) is a member of the ATF/cAMP response element-binding protein family. Our research group recently revealed that ATF5 expression increases the invasiveness of human lung carcinoma cells. However, the effects of ATF5 on the invasive potential of other cancer cells lines remain unclear.Therefore, in this study, we investigated the role of ATF5 in the invasive activity of diverse human cancer cell lines. Invasiveness was assessed using Matrigel invasion assays. ATF5 knockdow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 20 publications
2
19
0
1
Order By: Relevance
“…Some of uORF-containing genes, such as ATF5 and DDIT3, were also subject to DDX3-mediated translation control. ATF5 knockdown indeed disrupted cell invasion in diverse cancer cell lines (36). Thus, DDX3 is able to multiply its effect on activating a specific axis of ATF4 signaling to promote cell invasion (Fig.…”
Section: Discussionmentioning
confidence: 84%
“…Some of uORF-containing genes, such as ATF5 and DDIT3, were also subject to DDX3-mediated translation control. ATF5 knockdown indeed disrupted cell invasion in diverse cancer cell lines (36). Thus, DDX3 is able to multiply its effect on activating a specific axis of ATF4 signaling to promote cell invasion (Fig.…”
Section: Discussionmentioning
confidence: 84%
“…In contrast, the marked reduction in the activation of PI3K/Akt signaling pathway, as evidenced by decreased p-Akt levels, may indicate a reduced proliferation rate of ATF5-KD mammary tumor cells. Importantly, previous studies, investigating the role of ATF5 in survival of breast cancer cell lines, have focused so far on experiments performed in vitro , such as proliferation, migration, and apoptosis assays, and intracellular mechanisms by which ATF5 may exert its effects (16, 22, 28, 29). Therefore, to our knowledge, we show here for the first time that ATF5 downregulation leads to a decreased mammary tumor growth in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Very few studies have reported the association between ATF5 expression and cell motility. Among them, Nukuda et al performed an invasion assay in highly invasive cell lines, such as human HT-1080 fibrosarcoma, A549 lung cancer, and MDA-MB-231 breast cancer, and revealed that ATF5 knockdown reduces the invasiveness of these cells (29). Moreover, the authors showed that ATF5 expression was markedly increased in the invasive MDA-MB-231 cells than in the less invasive breast cancer cell line, MCF-7.…”
Section: Discussionmentioning
confidence: 99%
“…ATF5 also regulates growth and metabolism coordinating factors such as EGR1, mTOR and FGF21, as well as the mitochondrial-protective genes outlined above [59, 101103]. In addition to pro-growth and anti-apoptotic phenotypes, ATF5 contributes the resistance to radiotherapy [81] and the invasiveness of tumor cells by inducing integrin-α2 and integrin-β1 [96]. …”
Section: The Uprmt and Cancermentioning
confidence: 99%